MicroRNA‐21 (miR‐21) expression in hypothermic machine perfusate may be predictive of early outcomes in kidney transplantation. Issue 2 (5th January 2016) - Khalid, Usman; Ablorsu, Elijah; Szabo, Laszlo; Jenkins, Robert H.; Bowen, Timothy; Chavez, Rafael; Fraser, Donald J.
Abstract: Hypothermic machine perfusion is effective in improving outcome following kidney transplantation. Molecular analyses of hypothermic machine perfusate (HMP) have the potential to identify biomarkers of organ viability prior to transplantation, offering significant advantages to the transplant surgeon, and leading to a potential increase in the organ donor pool. MicroRNAs are emerging as important biomarkers in the context of kidney injury and transplantation. Recent data demonstrate increased microRNA‐21 (miR‐21) expression in the kidney following acute kidney injury. This study investigated the potential of miR‐21 detected in HMP to act as a sentinel for early kidney transplant outcomes. MiR‐21 was found to be readily detectable in HMP by RT‐qPCR. Eleven ECD kidneys were maintained on a hypothermic machine perfusion system for a median 627 (range 117–1027) minutes, and evaluation of flow and resistance characteristics suggested stability on the machine from 60 min post‐perfusion. MiR‐21 quantification at 60 min post‐perfusion correlated with eGFR at 6 and 12 months post‐transplantation. These data suggest that miR‐21 expression in HMP may be predictive of early outcomes following kidney transplantation. In the era of ECD kidneys, a reliable measure of organ quality is urgently needed, and this study suggests miR‐21 may be such a marker.